THE CREATION OF PUBLICATION MEDIA FOR RELIEF-PRINT ART EXHIBITION POST-COVID 19 - Adi, Sigit Purnomo; Aripin, Nur Adibah Nadiah Mohd; Marutama, I Gusti Ngurah Tri; Arissuta, Dona Prawita (ISI Press Institut Seni Indonesia Surakarta, 2024)
The creation of publication media for these relief-print artworks is a creative and innovative work because it does not only create relief-print works of art, but also creates publication media or exhibition media to exhibit relief-print works of art. This publication media work is a publication work that combines virtual and offline. The purpose of this work is the creation of relief-print art exhibition publication media that try to find alternative publication media which are environmentally friendly, efficient and global. The creation of this publication media uses the Tri Cipta Karya creation method which is an elaboration of the Artistic Creation method. The results of this creation produce an efficient Hybrid publication media, meaning that in the exhibition it is not only exhibited offline or physically, but also exhibited online or through a virtual gallery. The implications of this publication media creation have opened up wide opportunities for artists or designers to publish their works across countries online.